Islamic Education in Nigeria Public Schools: Challenges and The Way Forward - Wasilat Adigun (Presscience, 2025)
Islamic education is a vital component in the moral, spiritual, and intellectual development of Muslim students in Nigeria. While national policies mandate its inclusion in public schools to respect religious diversity, its practical implementation is hindered by significant challenges. This paper investigates the key obstacles confronting the effective delivery of Islamic education in Nigerian public schools. Using a qualitative approach that includes interviews and document analysis, the study identifies several critical issues: a lack of qualified teachers, inadequate instructional materials, curriculum inconsistencies, and the marginalization of Islamic Religious Studies (IRS). Furthermore, the research reveals that poor funding, insufficient motivation from government and society, and negative attitudes among some teachers adversely affect student engagement. A perception of the subject as inferior, held by some parents and authorities, further compounds these problems. To revitalize Islamic education, this paper proffers solutions centered on comprehensive teacher training programs, strategic curriculum reforms, and increased stakeholder engagement to ensure its successful integration and contribution to the national educational goals.